Evan syndrome as initial presentation of COVID-19 infection - Hamdy A. Mohammadien; Lotfy H. Abudab; Azza M. Ahmad (The Egyptian Journal of Bronchology, 2022)
Abstract Background Evans’ syndrome (ES) is a rare and chronic autoimmune disease characterized by the concomitant or sequential association of auto-immune hemolytic anemia (AIHA) with immune thrombocytopenia (ITP), and less frequently autoimmune neutropenia with a positive direct anti-human globulin test. ES represents up to 7% of AIHA and around 2% of ITP. Studies have found that coronavirus disease 2019 (COVID-19) may be associated with various hematological complications, i.e., coagulopathies; however, finding of Evans syndrome is a novel case. Case report A 54-year-old diabetic man complaining of fever (high grade), arthralgia and myalgia, fatigue, and dark color of urine. He was admitted to isolation sector at Sohag General Hospital on day 6 because of fever with cough, dyspnea, and progressive fatigue, and at admission, he was tachypneic, tachycardiac, jaundiced, febrile (38 °C), and hypoxemic (O2 saturations on room air was 80%). Laboratory studies showed hemoglobin (Hb) 5.43 g/dL, high reticulocyte (12.5%), ↓ed platelet count (54 × 103/μl), hyperbilirubinemia and elevated C-reactive protein (CRP), D-dimer, ferritin, and lactate dehydrogenase. Markers of autoimmune diseases and screening for malignant diseases were negative. HRCT chest showed bilateral small-sized peripheral ground glass opacities in both lungs, with positive reverse transcriptase-polymerase chain reaction (RT-PCR) for SARS-CoV-2 RNA in the nasopharyngeal swab. Direct Coombs test was positive for immunoglobulin (IgG) and C3d. Evans syndrome secondary to COVID-19 was diagnosed and treatment with packed red cell (PRC) transfusions, favipiravir, dexamethasone, prednisone, ceftriaxone, enoxaparin, oral hypoglycemic, and oxygen using face mask, and then Hb value increased to 10.3 g/dL and he was discharged home without any complications. Conclusion There are few reports of patients with concurrent COVID-19 and Evans syndrome. So, SARS-CoV-2 infection should be considered in any patient presenting with new-onset ES of unclear etiology.